2013
DOI: 10.1038/ijo.2013.198
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological assessment as a predictor of weight loss in obese adolescents

Abstract: This study highlights the potential to identify those who are obese by using an easy-to-measure psychometric test. Furthermore, it is the first study to report a reduction in impulsivity and an improvement in well-being as part of a government-approved residential camp for obese adolescents. The potential mechanisms for change in impulsivity with weight are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
64
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 43 publications
9
64
2
1
Order By: Relevance
“…The current literature examining the link between impulsivity and eating disorders has focused largely on BED and obesity (e.g., Davis et al, 2010;Kulendran et al, 2014;Manasse et al, 2015;Weller et al, 2008, etc.). For example, one study examined being at risk for eating disorders and impulsivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current literature examining the link between impulsivity and eating disorders has focused largely on BED and obesity (e.g., Davis et al, 2010;Kulendran et al, 2014;Manasse et al, 2015;Weller et al, 2008, etc.). For example, one study examined being at risk for eating disorders and impulsivity.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of women, those at risk for an eating disorder were more depressed and more impulsive on a delay discounting task than those not at risk for an eating disorder (Scherr, Ferraro, & Weatherly, 2010). Other researchers have also found that having or being at risk for eating disorders and obesity are both related to poor impulse control (Kulendran et al, 2014;Manasse et al, 2015;Scherr et al, 2010;Waxman, 2009). However, relationships between obesity and delay discounting are more consistent in females relative to males (Weller, Cook, Avsar, & Cox, 2008).…”
Section: Introductionmentioning
confidence: 86%
“…Many studies show connection between obesity and mood disorders. Obese patients present elevated impulsivity and loss of impulse control (Kulendran et al, 2014). One study that consisted of 571 patients with major depressive disorders showed that obese (BMI 430) individuals more frequently belonged to the bipolar group and had lower level of education compared to non-obese (BMI o30) subjects (Vannucchi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The stop signal task procedure was adapted from the method described by Logan et al (9,29) and involved participants sitting, facing the tablet screen, wearing headphones, with their index fingers resting on the two buttons of the controller. Arrows that pointed either left or right appeared on the screen and participants were instructed to press the corresponding button as quickly as possible, unless they heard a noise, in which case they were instructed to refrain from pressing any button.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, a positive association between childhood obesity and impulsivity has been demonstrated (7,9,10), and more impulsive participants have been found to lose less weight in obesity interventions (7,11).…”
Section: Introductionmentioning
confidence: 99%